(untitled) (PerCursos, 2022)
Since the 2000s, the proposal to recognize geoparks as territories that promote the heritage of the Earth and sustain local communities through the conservation and sustainable use of their heritage has been established as a new paradigm in terms of territorial development. In this sense, the objective of this article is to present the most relevant geopatronal and landscape aspects inventoried in the territory of the Fourth Colony (RS), as well as the construction trajectory of this project until the submission of the application dossier to the UNESCO World Geopark. The territory consists of nine municipalities, with just over sixty thousand inhabitants, extending for 2,923 km², demarcating the transition between the Brazilian Southern Plateau and the Peripheral Depression from Rio Grande do Sul. The main geopatrimonial highlight is the presence of one of the most important fossiliferous assemblies of the Triassic world. Added to this is the great diversity of natural landscapes found in the territory and the integrity of the cultural heritage associated with the migratory waves of the nineteenth century in the region, especially Italians and Germans. The territory dossier has 31 geosites of geopatrimonial value (distributed among the categories of fossiliferous, lithological/sedimentological, fluvial/hydrogeological and geomorphological value) and 23 sites linked to other forms of patrimonial value (ecological, scenic, historical-cultural and/or archaeological value). The article discusses, at the end, the strategies currently underway for a holistic management of the territory and its heritage.